Assisted Reproductive Technology and Birth Defects: Effects of Subfertility and Multiple Births. Issue 14 (21st June 2017) - Liberman, Rebecca F.; Getz, Kelly D.; Heinke, Dominique; Luke, Barbara; Stern, Judy E.; Declercq, Eugene R.; Chen, Xiaoli; Lin, Angela E.; Anderka, Marlene
Abstract : Background: Assisted reproductive technology (ART) has been associated with birth defects, but the contributions of multiple births and underlying subfertility remain unclear. We evaluated the effects of subfertility and mediation by multiple births on associations between ART and nonchromosomal birth defects. Methods: We identified a retrospective cohort of Massachusetts live births and stillbirths from 2004 to 2010 among ART‐exposed, ART‐unexposed subfertile, and fertile mothers using linked information from fertility clinics, vital records, hospital discharges, and birth defects surveillance. Log‐binomial regression was used to estimate prevalence ratios and 95% confidence intervals (CIs). Mediation analyses were performed to deconstruct the ART‐birth defects association into the direct effect of ART, the indirect effect of multiple births, and the effect of ART‐multiples interaction. Results: Of 17, 829 ART‐exposed births, 355 had a birth defect, compared with 162 of 9431 births to subfertile mothers and 6183 of 445, 080 births to fertile mothers. The adjusted prevalence ratio was 1.5 (95% CI, 1.3–1.6) for ART and 1.3 (95% CI, 1.1–1.5) in subfertile compared with fertile deliveries. We observed elevated rates of several birth defects with ART, including tetralogy of Fallot and hypospadias. Subfertility and multiple births affect these associations, with multiple births explaining 36% of the relative effect of ART on nonchromosomal birth defects. Conclusion: Although the risk of birth defects with ART is small, a substantial portion of the relative effect is mediated through multiple births, with subfertility contributing an important role. Future research is needed to determine the impact of newer techniques, such as single embryo transfer, on these risks. Birth Defects Research 109:1144–1153, 2017. © 2017 Wiley Periodicals, Inc.